Azaepothilone B and its derivatives: a patent review. (2nd August 2016) - Mandhare, Anita; Biradar, Satish; Gurule, Asha
ABSTRACT: Introduction : Azaepothilone B, also known as ixabepilone, is a semi synthetic second generation epothilone B analogue. Azaepothilone B, its derivatives, and analogues, are used for treating advance metastatic breast cancer. It has been used as a chemotherapeutic medication for cancer. Areas covered : This review highlights the patents on different routes for synthesis of azaepothilone B, its derivatives and analogues. The review will also provide the reported pharmacological activity and its polymorphs in the treatment of several cancers, such as breast cancer (metastatic or locally advanced), non-Hodgkin's lymphoma, and pancreatic cancer. In addition, it considers other proliferative diseases such as viral infections, degenerative diseases of the musculoskeletal system, kidney disease, and immune response related diseases. Different databases such as Espacenet, ISI Web of Knowledge, Patbase, and Thomson Innovation have been searched extensively to review the patents. The analysis has been done to indicate the patenting trend across years and the comparison of active assignees. Expert opinion : Azaepothilone B, along with its derivatives and analogues, can damage cancer cells in very low concentrations and retain its activity when tumor cells are insensitive to paclitaxel. Hence, it is highly potent agent. Azaepothilone B alone, in combination with other chemotherapeutics, or in the form of formulations, led to applications in various types of cancer. Also, antiproliferative activity of azaepothilone B has great potential for the treatment of proliferative diseases, such as skin diseases and infections. Recent progress in synthesizing azaepothilone B has encouraged researchers to develop new methods for the synthesis of azaepothilone B, its derivatives, and analogues, to obtain maximum yield in minimum steps.